Analysis of Cost Overrun & Time Overrun Causal Factors Affecting Construction Project Cost Performance Using Dematel & ANP - Adryani, Ayu; Taufik , Tatang Akhmad; Armono, Haryo Dwito (Dinasti Publisher, 2024)
The estimation of project costs and completion timelines are crucial aspects that need to be accurately predicted, as they are key indicators of a project's success. Issues like cost overruns and delays in project completion have become common in the construction industry. PT XYZ, a mining construction company, encountered a cost overrun in May 2023, leading to a 21.6% increase in the budget. According to the initial project baseline, it was expected to be completed by September 2023, but faced an 8-month delay. This study aims to explore the external factors causing cost and time overruns, identify the most significant factors, and propose recommendations to reduce these issues. The research methods used are Decision Making Trial and Evaluation Laboratory (DEMATEL) and Analytical Network Process (ANP) to examine the relationship between the factors and determine the most dominant one. Data was collected through questionnaires, and a threshold was set via a Focus Group Discussion (FGD) with experienced professionals in construction who played a key role in project decisions. The DEMATEL analysis, with a threshold of 0.5000, produced a relationship diagram of the criteria, and the ANP analysis, conducted using SuperDecisions software, revealed that the most influential factor affecting cost and time overruns is the accuracy of the Scope of Work (SOW) . As a result, it is recommended that PT XYZ improve project management and ensure higher accuracy in defining the SOW for future projects